Christina Rossetti : a writer's life - Marsh, Jan, 1942- (New York : Viking, 1995)
This, the first full-scale biography of Rossetti, reinstates her in her rightful place as a luminary among Victorian poets. Like Emily Dickinson, with whom she is often compared, Rossetti is a poet's poet who wrote some of the Victorian period's most lush, most original, and also some of its most restrained poetry.
Because of the new appreciation for this highly accomplished work, and also because, through her brother Dante Gabriel Rossetti, Christina is so closely associated with the Pre-Raphaelites and their superb art and bohemian lives, there had been a resurgence of interest in this enigmatic writer.
Here we learn of the deep sexual passions and ambivalence of her young adulthood; the men she chose and later denied; the warmth of her family life; her close ties to the grand literary figures of Victorian London; the religious devotion that suffused her later years; and her frustrated ambition to fulfill her life as an artist and a woman. Drawing on unread works and newly available letters, Marsh also makes sense for the first time of Rossetti's adolescent breakdown and recurrent depressions.
Includes bibliographical references and index.
Keywords: Rossetti, Christina Georgina, -- 1830-1894 -- Biography; Women poets, English -- 19th century -- Biography